Smell dysfunction resulting from COVID-19: An integrative literature review (Research, Society and Development, 2023)
Introduction: there are reports of a manifestation secondary to infection and viral action in the body: smell disorders and, consequently, taste disorders, which are present even before the molecular confirmation of the infection caused by SARS-CoV-2. Objective: to answer what are the mechanisms of olfactory disorders resulting from Covid-19, as well as risk factors and possible interventions. Methodology: This is a descriptive research of the integrative literature review type. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, August 2021. Results: The mechanisms of olfactory disorders related to SARS-CoV-2 infection are still unknown, but it is probably the result of various patterns, such as nasal mucosa edema, olfactory epithelial damage and even involvement of the central olfactory pathways. It was demonstrated that the expression of angiotensin-converting enzyme (ACE2) was found in the basal layer of the non-keratinizing squamous epithelium in the nasal and oral mucosa and in the nasopharynx. Conclusion: There may be olfactory-gustatory disturbances in variable intensities and prior to the general symptoms of Covid-19, they should be considered as part of the disease's symptoms, even in mild conditions. There is still no scientific evidence of specific treatments for such disorders in Covid-19, and it is important that further studies achieve, through clinical empiricism, better workup for these cases, especially those that manifest as a lasting sequelae of SARS-CoV-2 infection.